Метод обернено-опуклого програмування та оптимальне пакування вантажів - Ostapenko, V. V.; Sobolenko, L. A.; Prokhorovich, I. V. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
Formalization of the problem for optimal goods packing for an airplane is proposed. To solve the problem, the method of inverse-convex programming is used. Numerical calculations of test and real problems are presented.